Application of graphene oxide IoNanofluid as a superior heat transfer fluid in concentrated solar power plants. (February 2020) - Hosseinghorbani, Armin; Mozaffarian, Mehrdad; Pazuki, Gholamreza
Abstract: This study presents the fabrication of a highly stable Ionic liquid nanofluid (IoNanofluid) without any surfactant application by dispersing 0.5%, 1% and 2% mass fractions of functionalized graphene oxide (GO) nanoparticles in 1-butyl-3-methylimidazolium-bis(trifluoromethylsulfonyl)imide ([Bmim][NTf2 ]). Various analyses were employed to investigate the chemical structure and morphology of the synthesized nanoparticles. Dynamic light scattering (DLS) and transmission electron microscopy (TEM) results were taken into account to assess the stability of IoNanofluid. Thermophysical properties of the IoNanofluid including density, viscosity, thermal conductivity and specific heat capacity were measured experimentally, and compared with the base fluid's experimental data. The results showed the dramatic improvement of thermal conductivity and specific heat capacity of up to 6.5% and 27%, respectively. Therefore, application of the prepared IoNanofluid in concentrated solar power (CSP) plants as heat transfer fluid (HTF) could lead to enhancement of the overall efficiency of the system. Accordingly, in order to estimate the heat transfer performance of IoNanofluid, Dittus-Boelter, the correlation commonly used for turbulent flow was applied. Compared to the base fluid, the maximum heat transfer coefficient enhancement was 7.2% via application of 0.5% mass fraction of GO nanoparticles. Thus, it seems that GO IoNanofluid at low mass fractions has desirable advantages for using as HTF in CSP plants. Highlights: Functionalized graphene oxide (GO) nanoparticles are Synthesized and characterized. Ionic liquid nanofluid based on GO is prepared. Thermal conductivity and specific heat of IoNanofluid are enhanced. Heat transfer coefficient of GO IoNanofluid is improved.